A new species and new records of Cybaeus L. Koch, 1868 (Aranei: Cybaeidae) in the Maritime Province of Russia - Marusik Yuri M.; Omelko Mikhail M. (KMK SCIENTIFIC PRESS LTD, MOSCOW STATE UNIV, 2022)
A survey of Cybaeidae in Far East Russia reveals three additional species: two species recently described from northeastern China, C. fushun Lin et Li, 2021 and C. huadian Lin et Li, 2021, and one species new to science, C. mikhailovi sp.n. (male female). Females of C. fushun and C. huadian are redescribed And the previously unknown male of C. fushun is described for the first time.